Hubungan Antara Tingkat Keharmonisan Keluarga Dan Kematangan Terhadap Emosional Anak Kelas X Akuntansi Di SMK Tadika Pertiwi Cinere Depok - Yanti Haryantini (Thawalib: Jurnal Kependidikan Islam, 2020)
The purpose of this study was to determine: 1). Want to get information objectively about the relationship between the level of family harmony and the emotional maturity of students at Taraka Pertiwa Cinere Junior High School, and 2). Knowing the relationship between family harmony and students' emotional abilities                Samples were taken by random sampling of 80 students, taken from each class of 10 students. There are two variables studied, namely family harmony as the independent variable and student emotional maturity as the dependent variable. The data were collected using a questionnaire and a psychological scale. The data obtained were analyzed using product moment correlation analysis.                The results of the percentage descriptive analysis showed that the family harmony of students at Taraka Pertiwa Cinere Junior High School was in moderate criteria, namely with a percentage of 67.34%, while the emotional maturity of students was considered moderate, namely with a percentage of 67.96%, the results of the correlation analysis obtained a correlation coefficient of 0.459. At a = 5% with N = 80 obtained t table = 0.220 because rcount = 0.459> r table = 0.220, which means there is a relationship between family harmony and emotional maturity of students at Taraka Pertiwa Cinere Junior High School.